Searching for a better deal: On the influence of group decision making, time pressure and gender in a search experiment - Marcela Ibanez; Simon Czermak; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2008)
We study behavior in a search experiment where sellers receive randomized bids from a computer. At any time, sellers can accept the highest standing bid or ask for another bid at positive costs. We find that sellers stop searching earlier than theoretically optimal. Inducing a mild form of time pressure strengthens this finding in the early periods. There are marked gender differences. Men search significantly shorter than women. If subjects search in groups of two subjects, there is no difference to individual search, but teams of two women search much longer than men and recall more frequently.
Keywords: C91; C92; D83; 330; search experiment; time; group decision; gender differences; Gruppenentscheidung; Dauer; Geschlecht; Suchtheorie; Test